(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The objective of this work is to describe the experiences that are being carried out with the implementation of a Virtual Evidence Portfolio (PEV) in the Wix platform, in the Academic Division of Administrative Economic Sciences (DACEA), as well as a learning, autonomous and participatory. The research is of a cross-sectional descriptive type, the study variables are according to the instrument adapted from Canalejas (2010) with 27 items. 98 students of all cycles were surveyed, of which 56% were women and 44% men, of which 30% were between 18 and 20 years old, 26% were between 21 and 23 and 25 % were older than 24 years. The results show that the VEP in students is a creativity enhancer (3.35), increases their autonomy for study (3.05), motivates their personal life (3.02), identifies their strengths and weaknesses (3.2) and allows them to have a complete academic progress (3.12). Finally, we can conclude that the virtual evidence portfolio is a tool that has had an increase in its use in educational institutions at different educational levels. That is why in our division and university they are being used more and more by teachers as an element of evidence and a factor for evaluating learning by competencies.